Transition from Tradition to Modernity: Health Challenges for Coastal Communities in Pematang Cengal Village - Dita, Dita; Diva, Diva; Ikrima, Ikrima; Khairunnisa, Khairunnisa; Nabila, Nabila; Wafida, Wafida; Wasiyem, Wasiyem (CV. Rayyan Dwi Bharata, 2025)
Society is always experiencing change, and changes that occur in society are natural and unavoidable, even though changes in one society will be different from changes in other societies. Likewise with the modernization process. According to